Contexts as Shared Commitments - García-Carpintero, Manuel (Frontiers in Psychology, 2015)
Contemporary semantics assumes two influential notions of context: one coming from Kaplan (1989), on which contexts are sets of predetermined parameters, and another originating in Stalnaker (1978), on which contexts are sets of propositions that are “common ground.” The latter is deservedly more popular, given its flexibility in accounting for context-dependent aspects of language beyond manifest indexicals, such as epistemic modals, predicates of taste, and so on and so forth; in fact, properly dealing with demonstratives (perhaps ultimately all indexicals) requires that further flexibility. Even if we acknowledge Lewis (1980)'s point that, in a sense, Kaplanian contexts already include common ground contexts, it is better to be clear and explicit about what contexts constitutively are. Now, Stalnaker (1978, 2002, 2014) defines context-as-common-ground as a set of propositions, but recent work shows that this is not an accurate conception. The paper explains why, and provides an alternative. The main reason is that several phenomena (presuppositional treatments of pejoratives and predicates of taste, forces other than assertion) require that the common ground includes non-doxastic attitudes such as appraisals, emotions, etc. Hence the common ground should not be taken to include merely contents (propositions), but those together with attitudes concerning them: shared commitments, as I will defend.